A systematic appraisal on catalytic synthesis of 1, 3-oxazole derivatives: A mechanistic review on metal dependent synthesis. Issue 1 (2nd January 2022) - Shinde, Suraj R.; Girase, Pankaj; Dhawan, Sanjeev; Inamdar, Shaukatali N.; Kumar, Vishal; Pawar, Chandrakant; Palkar, Mahesh B.; Shinde, Mahadev; Karpoormath, Rajshekhar
Abstract: 1, 3-Oxazole, is a distinctive five-membered nitrogen and oxygen containing heterocyclic compound. The versatility of this heterocyclic ring system makes it as an important class of heterocyclic compounds. Consequently, the compounds or derivatives containing 1, 3-oxazole scaffold are reported to possess wide variety of applications in medicinal, pharmaceutical, agrochemical, and material sciences. In recent years several potent molecules containing1, 3-oxazole as a core sub-unit of the structural frame, have been reported, leading to the significant increase in number of research articles published to explore its broad utility and versatility. Further, it has caught the attention of chemists globally to develop new methodologies for the synthesis of novel promising substituted 1, 3-oxazole derivatives as building blocks. However, to date, there is no specific review on 1, 3-oxazole and it's derivatives with special emphasis on it's synthetic methodology strategies and applications. We have collected total of 30 research articles published in peer-reviewed international journals in last 4 years with special emphasis on metal dependent synthetic methodology of 1, 3-oxazole derivatives. Hence, this review is our sincere effort to comprehensively represent the systematic interpretation of literature describing the metal based catalytic strategies for 1, 3-oxazole derivatives. We expect that our review will certainly benefit organic chemists to recognize the challenges in the methods, assist them in the selection of reactants and developing new 1, 3-oxazole analogues using various metal catalyst. Graphical Abstract: UF0001